1991
DOI: 10.1063/1.859642
|View full text |Cite
|
Sign up to set email alerts
|

Global confinement and discrete dynamo activity in the MST reversed-field pinch

Abstract: Results obtained on the Madison Symmetric Torus (MST) reversed-field pinch [Fusion Technol. 19, 13 1 ( 199 1) ] after installation of the design poloidal field winding are presented. Values of Be, = 2~, nd) T&/B s (a) -12% are achieved in low-current (I = 220 kA) operation; here, n, and T, are central electron density and temperature, and Be (a) is the poloidal magnetic field at the plasma edge. An observed decrease in pod) with increasing plasma current may be due to inadequate fueling, enhanced wall intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 18 publications
8
62
0
Order By: Relevance
“…[1][2][3] Similar to the case in tokamaks, the RFP sawtooth crash coincides with a sudden transfer of energy from the core plasma to the edge and is interpreted as magnetohydrodynamic ͑MHD͒ relaxation. During the slow sawtooth rise phase in the RFP, the profile, where (r)ϭ 0 J-B/B 2 , peaks as a result of resistive diffusion and the peaked parallel equilibrium inductive electric field.…”
mentioning
confidence: 90%
“…[1][2][3] Similar to the case in tokamaks, the RFP sawtooth crash coincides with a sudden transfer of energy from the core plasma to the edge and is interpreted as magnetohydrodynamic ͑MHD͒ relaxation. During the slow sawtooth rise phase in the RFP, the profile, where (r)ϭ 0 J-B/B 2 , peaks as a result of resistive diffusion and the peaked parallel equilibrium inductive electric field.…”
mentioning
confidence: 90%
“…Studies of the scrape-off layer (SOL) plasma have found that temperature scale lengths and floating potential scale with n/I P [34,35]. In RFPs, I/N provides a good scaling parameter for Z EFF and β [36]. Finally, note that the critical N β for the onset of tearing modes can be scaled with n/ n G .…”
Section: Physics Correlated With the Density Limit Scalingmentioning
confidence: 99%
“…Pellet fueling in RFX allowed the limit to be overcome, but only transiently. The I/N ratio has proved to be a good scaling quantity for other phenomena in the RFP, including the plasma β, Z EFF , energy confinement [185,36] and the low density limit [174,175]. Poor performance at low density (high I/N) has been attributed to instabilities driven by large values of the streaming parameter V DRIFT /V THERMAL [174].…”
Section: Reversed Field Pinchmentioning
confidence: 99%
“…Measurements were performed in the relatively low plasma current discharges to avoid heat damage to the inserted probes. All measurements were taken around the current flattop period, in which MST discharges typically show the discrete sawtooth oscillations with several millisecond repetition period 18 while REPUTE and TPE discharges contain rather irregular oscillations.…”
Section: Experimental Apparatusmentioning
confidence: 99%